Sosialisasi Pencegahan DBD (Demam Berdarah Dengue) pada Masyarakat Desa Sumuranja Pulo Ampel Serang - Khofiyya, Nida’an; Firdaus, Ridho; Kamalia, Nilna; Nurohmah, Titin; Juniadi, Aldi; Indriyanti, Devi (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue virus infection transmitted through the bite of the Aedes aegypti mosquito which is characterized by sudden fever, headache, pain behind the eyeball, nausea and bleeding manifestations such as positive tourniquet (rumple lead) tests, red spots on the skin (petekie), nosebleeds, bleeding gums and so on. Implementation Of the method used in this activity is Socialization (Counseling) with lectures and questions and answers. Lectures were conducted to socialize information about epidemics, eradication and dengue management. The purpose of this activity is to provide public knowledge and understanding of the dengue epidemic in their environment and provide community knowledge and understanding of dengue fever management and eradication in the surrounding environment. The socialization of dengue disease prevention and eradication activities has been carried out well and the participants were very enthusiastic in participating in the activity. Most of the participants understood the material presented on how to prevent and eradicate dengue disease